Pengaruh Kompetensi Auditor, Pelaksanaan Pengendalian Internal, Ukuran dan Kompleksitas Perusahaan terhadap Kualitas Audit Eksternal pada Perusahaan Publik di Indonesia - Syarifudin, Jasmine Ashila Humairah; Syofyan, Efrizal (Universitas Negeri Padang, 2025)
This study examines how auditor competence, internal control, company size, and complexity affect external audit quality. It uses a causal research design with a quantitative approach, analyzing annual reports from 102 manufacturing firms between 2021 and 2023. Using logistic regression analysis,the findings reveal that auditor competence and internal control, while essential, do not independently improve audit quality due to perfect prediction issues, and company size and complexity also show no significant effect. However, all variables together do influence audit quality, highlighting that basic factors alone are not enough audit quality depends more on standard compliance and external factors. This study contributes new insights by challenging common assumptions about audit quality drivers and pointing out methodological challenges, offering valuable guidance for future research.